2022
DOI: 10.1158/2159-8290.cd-21-1141
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Pembrolizumab versus IFNα2b or Ipilimumab in Resected High-Risk Melanoma

Abstract: We conducted a randomized phase III trial to evaluate whether adjuvant pembrolizumab for one year (647 patients) improved recurrence-free survival (RFS) or overall survival (OS) in comparison with high-dose IFNα-2b for one year or ipilimumab for up to three years (654 patients), the approved standard-of-care adjuvant immunotherapies at the time of enrollment for patients with high-risk resected melanoma. At a median follow-up of 47.5 months, pembrolizumab was associated with significantly longer RFS than prior… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 24 publications
0
52
0
2
Order By: Relevance
“…9 Both PD-1 inhibitors-nivolumab and pembrolizumab-have now been compared with ipilimumab in separate trials and have shown an improvement for RFS; to date, however, they have not shown an improvement for OS. 7,10 The reason for this is unclear but possibly affected by postrelapse treatment, insufficient follow-up, or biologic and immune issues not yet fully understood. It is not clear how to interpret all this in the context of what we know about the proven survival benefits of immune checkpoint inhibitor therapy for patients with metastatic disease.…”
Section: Current State Of Adjuvant Immune Checkpoint Inhibitor Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…9 Both PD-1 inhibitors-nivolumab and pembrolizumab-have now been compared with ipilimumab in separate trials and have shown an improvement for RFS; to date, however, they have not shown an improvement for OS. 7,10 The reason for this is unclear but possibly affected by postrelapse treatment, insufficient follow-up, or biologic and immune issues not yet fully understood. It is not clear how to interpret all this in the context of what we know about the proven survival benefits of immune checkpoint inhibitor therapy for patients with metastatic disease.…”
Section: Current State Of Adjuvant Immune Checkpoint Inhibitor Therapymentioning
confidence: 99%
“…Similarly, the predominant site of failure in the SWOG-S1404 trial was distant, being reported in 60% of patients in the pembrolizumab arm vs. 71% of those who received standard-of-care therapy. 10 The presence of liver and brain metastasis is linked to poor prognosis for patients with advanced melanoma who are treated with anti-PD1 agents, either as monotherapy or combined with ipilimumab. 25 Although combination checkpoint inhibition has demonstrated excellent efficacy for asymptomatic patients with brain metastases from melanoma, the intracranial response rate and prognosis for those with symptoms or who require steroids are far from satisfactory, with substantial compromise of quality of life.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…7 %), Nebenniereninsuffizienz (ca. 2,5 %) und Hypophysitis (1–2 %) beschrieben; auch höhergradige Toxizitäten (Grad 3/4) werden beobachtet (insgesamt 6–11 %; [ 9 , 10 , 12 – 15 , 17 , 23 ]). PD-L1 wird sowohl auf Immunzellen (T-, B‑Zellen, Monozyten, APC [„antigen presenting cells“]) als auch auf epithelialen Zellen exprimiert und ist einer der beiden spezifischen Liganden von PD‑1 [ 3 ].…”
Section: Introductionunclassified
“…7 %), Nebenniereninsuffizienz (ca. 2,5 %) und Hypophysitis (1–2 %) beschrieben; auch höhergradige Toxizitäten (Grad 3/4) werden beobachtet (insgesamt 6–11 %; [ 9 , 10 , 12 – 15 , 17 , 23 ]).…”
Section: Introductionunclassified
“…Blockade in Resected Melanoma: Is Preventing Recurrence Enough?James W. Smithy 1 and Alexander N. Shoushtari1,2 …”
mentioning
confidence: 99%